Arabic Language Education Program at Islamic Boarding School Ibnul Qoyyim Putri Yogyakarta: Study of Code Mixing, Code Switching, and Interference - Muhajir; Karomah, Siti (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
This study aims to determine code-mixing, code-switching, and Arabic interference in the Arabic language education program at the Ibnul Qoyyim Putri Islamic Boarding School in Yogyakarta. It is based on two arguments; First, code-mixing, code-switching, and language interference are language “diseases” that are sociological and will be hereditary, especially in a particular program. So far, studies on sociolinguistics have separated code-mixing, code-switching, and interference, even though all three are interrelated. This study raises two issues: the forms of code-mixing, code-switching, and interference, and the causes of these three things. This research is qualitative research, with the methods used in this research being observation, interviews, and documentation. While the theory used is Fishman’s sociolinguistic theory of language in a socio-cultural context. The results of this study indicate that; First, code-switching that occurs in Arabic education programs Pondok Pesantren Ibnul Qoyyim Putri Yogyakarta is a form of code-switching at the word and phrase level, while the code-mixing that occurs is at the word level. The interference that occurs includes phonological, morphological, syntactic, and semantic interference. Second, code-switching, mixing, and interference in Arabic language education programs are caused by the instructors’ lack of a correct model and inadequate mastery of Arabic theory.